Explaining the birth order effect: The role of prenatal and early childhood investments - Jee-Yeon K. Lehmann; Ana Nuevo-Chiquero; Marian Vidal-Fernández (Institute for the Study of Labor (IZA), 2012)
The critical role of prenatal and early childhood conditions on adult outcomes has been the focus of a rich body of research. In this paper, we examine various pre- and postnatal investments as possible sources behind the birth order effect - significant differences in the educational and labor market outcomes across children of varying birth orders. Taking advantage of a rich set of information on in utero and early childhood conditions in the Children of the NLSY79, we find that, within the same household, siblings of higher birth order experience a lower reduction in cigarette usage during pregnancy, are breastfed less often, and experience less cognitive stimulation and emotional support at ages 0 to 1. Next, we test for the presence of birth order effects in early cognitive and non-cognitive test scores and examine whether these differences can be explained by variations in prenatal and early childhood investments. Although there exists a significant negative relationship between birth order and early cognitive/non-cognitive test scores, the size and the significance of the negative birth order effects in test scores and educational attainment are robust to controlling for variations in early childhood factors.
Keywords: J10; J13; I24; 330; birth order; early test scores; parental investment; prenatal investment; postnatal investment; early childhood investment; fetal origins hypothesis; cognitive outcomes; non-cognitive outcomes; Schwangerschaft; Kinderbetreuung; Frühkindliche Bildung; Kinder; Kognition; USA